Everolimus-Eluting Stents or Bypass Surgery for Multivessel Coronary Artery Disease: Extended Follow-Up Outcomes of Multicenter Randomized Controlled BEST Trial. Issue 21 (19th September 2022) - Ahn, Jung-Min; Kang, Do-Yoon; Yun, Sung-Cheol; Ho Hur, Seung; Park, Hun-Jun; Tresukosol, Damras; Chol Kang, Woong; Moon Kwon, Hyuck; Rha, Seung-Woon; Lim, Do-Sun; Jeong, Myung-Ho; Lee, Bong-Ki; et al.
Abstract : Background: Long-term comparative outcomes after percutaneous coronary intervention (PCI) with everolimus-eluting stents and coronary artery bypass grafting (CABG) are limited in patients with multivessel coronary artery disease. Methods: This prospective, multicenter, randomized controlled trial was conducted in 27 international heart centers and was designed to randomly assign 1776 patients with angiographic multivessel coronary artery disease to receive PCI with everolimus-eluting stents or CABG. After inclusion of 880 patients (438 in the PCI group and 442 in the CABG group) between July 2008 and September 2013, the study was terminated early because of slow enrollment. The primary end point was the composite of death from any cause, myocardial infarction, or target vessel revascularization. Results: During a median follow-up of 11.8 years (interquartile range, 10.6–12.5 years; maximum, 13.7 years), the primary end point occurred in 151 patients (34.5%) in the PCI group and 134 patients (30.3%) in the CABG group (hazard ratio [HR], 1.18 [95% CI, 0.88–1.56]; P =0.26). No significant differences were seen in the occurrence of a safety composite of death, myocardial infarction, or stroke between groups (28.8% and 27.1%; HR, 1.07 [95% CI, 0.75–1.53]; P =0.70), as well as the occurrence of death from any cause (20.5% and 19.9%; HR, 1.04 [95% CI, 0.65–1.67]; P =0.86). However, spontaneous myocardial infarction (7.1% and 3.8%; HR, 1.86 [95% CI, 1.06–3.27]; P =0.031) and any repeat revascularization (22.6% and 12.7%; HR, 1.92 [95% CI, 1.58–2.32]; P <0.001) were more frequent after PCI than after CABG. Conclusions: In patients with multivessel coronary artery disease, there were no significant differences between PCI and CABG in the incidence of major adverse cardiac events, the safety composite end point, and all-cause mortality during the extended follow-up. Registration: URL: https://www.clinicaltrials.gov ; Unique identifiers: NCT05125367 and NCT00997828.